Poly-(vinylpyrrolidone)-poly-(vinylacetate-co-crotonic acid) (PVP : PVAc-CA) interpolymer complex microparticles encapsulating a Bifidobacterium lactis Bb12 probiotic strain: microparticle characterization and effect on viability of encapsulated probiotic cells - Thantsha, Mapitsi Silvester (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.